'Tis the Gift. (Opera News, 2008)
The article reviews several personal home entertainment products, including the Bose 901 Series VI Direct/Reflecting Speaker System, the McIntosh MS750 Music Server, and the Panasonic PZ850 Viera high-definition television set.